“Y” and “X” Stent-Assisted Coiling of Complex and Wide-Neck Intracranial Bifurcation Aneurysms - Bartolini, B.; Blanc, R.; Pistocchi, S.; Redjem, H.; Piotin, M. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Stent-assisted coiling with two stents has been described in some series for the treatment of complex and wide-neck bifurcation aneurysms. Our aim was to report our experience of a stent-assisted coiling technique with double stents in “Y” and “X” configurations, with emphasis on safety, feasibility, and efficacy. MATERIALS AND METHODS: Clinical and angiographic outcomes of patients for whom the strategic therapeutic option was the stent-assisted coiling technique in a Y or X configuration for neck scaffolding from June 2006 to June 2013 were retrospectively analyzed. RESULTS: One hundred five aneurysms in 97 patients were treated during 100 consecutive procedures. There were 54.2% (57/105) MCA, 28.6% (30/105) anterior communicating artery, 16.2% (17/105) basilar tip, and 1.0% (1/105) ICA termination aneurysms. A Y stent placement was used to treat 87 aneurysms in 85 procedures; an X stent placement was used to treat 7 aneurysms in 6 procedures, while 9 procedures failed for 11 aneurysms. There were 10.0% (10/100) procedure-related permanent neurologic deficits and 1.0% (1/100) death. The immediate angiographic controls showed a complete occlusion in 47.6% (50/105) of the aneurysms and a partial (neck or sac remnant) occlusion in 52.4% (55/105). To date, 81.0% (85/105) of the aneurysms have been followed up (mean, 17 months) with angiography, disclosing a recanalization in 5.9% (5/85) and an improvement in 42.4% (36/85). At discharge and follow-up, the mRS score was 0 in 83.5% (81/97) of patients, 1 in 4.1% (4/97), 2 in 3.1% (3/97), 3 in 4.1% (4/97), 4 in 3.1% (3/97), and 6 in 2.1% (2/97). CONCLUSIONS: Y and X stent-assisted coiling of complex and wide-neck intracranial bifurcation aneurysms is an effective technique. AcomAanterior communicating artery